(untitled) (Itinera, 2024)
Performativity, connection, aggregate, conflict, Stimmung and artificial intelligence are among the topics chosen by the authors of the monographic issue of scientific journal Paradigmi, Rivista di Critica Filosofica dedicated to Connected images: New Paradigms for Aesthetic Experience, edited by Micaela Latini and Elena Tavani. Numerous contemporary and transdisciplinary forms of interpretation represent aesthetic experience in this Issue. It approaches the art world with Nature and the images naturally created by animals and natural environments (Tavani), the body in motion and its intentionality represented by images (Alloa, Benjamin), the body and time in tattoo images (Vercellone), the biological world and molecular discoveries (Bredekamp), furniture objects and the image of aesthetic experience they suggest (Goehr), political and social conflicts and what they represent (Latini), and pictures of music (Pangrazi). The last essays follow this mainly focused on the digital context, artificial intelligence and the technological impact on the art world and of chiasmus in images (Diodato), political rhetoric (Fimiani), surreal image interventions in the world of artificial intelligence (Somaini) and identity and the constitution of algorithms (Eugeni).